Patient Posture Affects Simulated ROM in Reverse Total Shoulder Arthroplasty: A Modeling Study Using Preoperative Planning Software. Issue 3 (March 2022) - Moroder, Philipp; Urvoy, Manuel; Raiss, Patric; Werthel, Jean-David; Akgün, Doruk; Chaoui, Jean; Siegert, Paul
Abstract: Background: Component selection and placement in reverse total shoulder arthroplasty (RTSA) is still being debated. Recently, scapulothoracic orientation and posture have emerged as relevant factors when planning an RTSA. However, the degree to which those parameters may influence ROM and whether modifiable elements of implant configuration may be helpful in improving ROM among patients with different postures have not been thoroughly studied, and modeling them may be instructive. Questions/purposes: Using a dedicated expansion of a conventional preoperative planning software, we asked: (1) How is patient posture likely to influence simulated ROM after virtual RTSA implantation? (2) Do changes in implant configuration, such as humeral component inclination and retrotorsion, or glenoid component size and centricity improve the simulated ROM after virtual RTSA implantation in patients with different posture types? Methods: In a computer laboratory study, available whole-torso CT scans of 30 patients (20 males and 10 females with a mean age of 65 ± 17 years) were analyzed to determine the posture type (Type A, upright posture, retracted scapulae; Type B, intermediate; Type C, kyphotic posture with protracted scapulae) based on the measured scapula internal rotation as previously described. The measurement of scapular internal rotation, which defines these posture types, was found to have a high intraclass correlation coefficient (0.87) in a previous study, suggesting reliability of the employed classification. Three shoulder surgeons each independently virtually implanted a short, curved, metaphyseal impaction stem RTSA in each patient using three-dimensional (3D) preoperative surgical planning software. Modifications based on the original component positioning were automatically generated, including different humeral component retrotorsion (0°, 20°, and 40° of anatomic and scapular internal rotation) and neck-shaft angle (135°, 145°, and 155°) as well as glenoid component configuration (36-mm concentric, 36-mm eccentric, and 42-mm concentric), resulting in 3720 different RTSA configurations. For each configuration, the maximum potential ROM in different planes was determined by the software, and the effect of different posture types was analyzed by comparing subgroups. Results: Irrespective of the RTSA implant configuration, the posture types had a strong effect on the calculated ROM in all planes of motion, except for flexion. In particular, simulated ROM in patients with Type C compared with Type A posture demonstrated inferior adduction (median 5° [interquartile range -7° to 20°] versus 15° [IQR 7° to 22°]; p < 0.01), abduction (63° [IQR 48° to 78°] versus 72° [IQR 63° to 82°]; p < 0.01), extension (4° [IQR -8° to 12°] versus 19° [IQR 8° to 27°]; p < 0.01), and external rotation (7° [IQR -5° to 22°] versus 28° [IQR 13° to 39°]; p < 0.01). Lower retrotorsion and a higher neck-shaft angle of the humeral component as well as a small concentric glenosphere resulted in worse overall ROM in patients with Type C posture, with severe restriction of motion in adduction, extension, and external rotation to below 0°. Conclusion: Different posture types affect the ROM after simulated RTSA implantation, regardless of implant configuration. An individualized choice of component configuration based on scapulothoracic orientation seems to attenuate the negative effects of posture Type B and C. Future studies on ROM after RTSA should consider patient posture and scapulothoracic orientation. Clinical Relevance: In patients with Type C posture, higher retrotorsion, a lower neck-shaft angle, and a larger or inferior eccentric glenosphere seem to be advantageous.